Spontaneous hepatic rupture during late pregnancy in a patient with solitary necrotic nodule of the liver: A case report - Wang, Jilong; Yi, Qilin; Guo, Ya; Peng, Tao (Frontiers in Medicine, 2022)
Background Spontaneous hepatic rupture (SHR) during pregnancy is a rare and life-threatening event, which usually occurs together with preeclampsia, eclampsia, HELLP syndrome, or liver tumors. However, SHR resulting from solitary necrotic nodule of the liver (SNNL) is extremely rare. Case presentation We report the case of a 32-year-old pregnant woman who presented at 33 weeks of gestation with abdominal pain and emesis. Transabdominal ultrasound and magnetic resonance imaging revealed massive hemoperitoneum and lesions in the left lobe of the liver. An emergency cesarean section was performed and the hepatic rupture was managed surgically via left lateral lobectomy. The postprocedural course was uneventful. The premature baby successfully survived, and the patient was discharged 8 days after admission without complications. Histological examination revealed a diagnosis of SNNL, which resulted in the hepatic hematoma and SHR. Conclusion To our knowledge, this is the first case of SHR resulting from SNNL during late pregnancy. Multidisciplinary collaboration and surgical management are important cornerstones for improving the perinatal outcomes when SHR is suspected in a pregnant patient.